Coronary artery disease in a rural population of Bangladesh: is dyslipidemia or adiposity a significant risk? - Banerjeel, Sajal Krishna; Ahmed, Chaudhury Meshkat; Rhaman, Mir Masudur; Chowdhury, Mohammad Mainul Hasan; Sayeed, M Abu (IMC Journal of Medical Science, 2017)
Background and Aims: The prevalence of cardiovascular diseases (CVD) are on the increase worldwide and more in the developing countries. Coronary artery disease (CAD) constitutes the major brunt of CVD. Despite the increasing morbidity and mortality, Bangladesh has a few published data on CAD in rural population. This study addressed the prevalence of CAD and its risk factors in rural population of Bangladesh. Study methods: Sixteen villages were purposively selected in a rural area. A population census was conducted in the selected area. The census yielded eligible participants, who reached at least eighteen years of age. Those who willingly consented to participate were enlisted. Each participant was interviewed regarding CAD risk (age, sex, social class, occupation, illness, family history). Anthropometry (height, weight, waist- and hip-girth) was recorded. Resting blood pressure (BP) was measured. Blood sample was collected for fasting blood glucose (FBG), total cholesterol (Chol), triglycerides (Tg), low density lipoproteins (LDL), very low density lipoproteins (VLDL) and high density (HDL). All participants having FBG>5.5mmol/l or systolic (SBP) ?135 or diastolic BP (DBP) ?85mmHg underwent electrocardiography (ECG). A team of cardiologists selected and accomplished exercise tolerance test (ETT) and echocardiography (Echo). Results: The prevalence of CAD was 4.5% (95% CI: 3.85 5.15). Compared with the female (3.5%, CI, 2.76 4.24) the male participants had significantly higher prevalence of CAD (6.0%, CI, 4.83 7.13). Comparison of characteristics between participants with and without CAD showed that age, SBP, DBP and FBG were significantly higher in CAD group. Bivariate analysis showed that age, sex, social class, glycemic status, metabolic syndrome (MetS) and smoking were significantly related to CAD. Stepwise logistic regression proved only male sex, rich social class, hypertension and diabetes had independent risk of CAD; whereas, age, obesity and dyslipidemia were proved not significant. Conclusions: The study concludes that the prevalence of CAD in a Bangladeshi rural population is comparable to other developed countries. The male sex, rich social class, hypertension and diabetes were proved to have excess risk of CAD. Neither obesity nor dyslipidemia were found significant for CAD. The younger people had similar risk as the aged ones, which necessitate primordial and primary prevention of CAD. Further study may be undertaken, which should include and consider physical activity and diet; and if possible, Creactive protein, Vitamin D and homocysteine level. IMC J Med Sci 2017; 11(2): 61-69